Methane and Nitrous Oxide Production From Agricultural Peat Soils in Relation to Drainage Level and Abiotic and Biotic Factors - Norberg, Lisbet; Hellman, Maria; Berglund, Kerstin; Hallin, Sara; Berglund, Örjan (Frontiers in Environmental Science, 2021)
Greenhouse gas emissions from drained agricultural peatlands contribute significantly to global warming. In a laboratory study using intact cores of peat soil from eight different sites in Sweden, factors controlling the emission of the greenhouse gases nitrous oxide (N2O) and methane (CH4) were examined. Soil properties, and the abundance of the total microbial community (16S rRNA gene abundance), and genes encoding for functions controlling N2O emissions (bacterial and archaeal amoA, nirS, nirK, nosZI, and nosZII) were analyzed and compared against measured greenhouse gas emissions. Emissions were measured at different drainage levels, i.e., higher soil water suction values, since drainage is an important factor controlling greenhouse gas emissions from peat soils. The results showed that N2O and CH4 emissions were generally low, except for N2O emissions at near water-saturated conditions, for which three soils displayed high values and large variations in fluxes. Relationships between N2O emissions and soil properties were mainly linked to soil pH, with higher emissions at lower pH. However, specific assemblages of nitrogen cycling guilds that included nosZII, typically present in non-denitrifying N2O reducers, were detected in soils with low N2O emissions. Overall, these results indicate that both pH and biotic controls determine net N2O fluxes.